Analisis Pengaruh Kepercayaan, Kualitas Produk, dan Kemudahan Berbelanja Terhadap Keputusan Membeli bagi Pelanggan Online Shop - Muhamad Khairul Anuar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The motivation behind this research is to decide and dissect the impact of trust, quality of goods, and ease of shopping on the purchasing choices of web-based shop clients in Kasu Village, Back District, Padang. The type of exploration used in this study is "Illustative Research", which is a type of examination that is expected to determine the size of the relationship and the impact of different variables, as well as or test the proposed (which is admittedly dismissed). The population in this study were buyers who had shopped online in Kasu Village, Back District of Padang. The testing procedure used is a non-probability check, the community components are selected based on their accessibility (eg because they intentionally want to be respondents) or based on their own analytical considerations that they can handle the community. The results of this study are generally felt that trust, quality of goods, community components are selected based on their accessibility (eg because they intentionally need to be respondents) or based on their own considerations that they can handle the community.